Pengaruh Konsentrasi Dan Waktu Aplikasi Pupuk Organik Cair Nasa Terhadap Pertumbuhan Dan Produksi Tanaman Jagung Manis Pada Tanah Sawah - Zulkarnain Sangadji (Median : Jurnal Ilmu Ilmu Eksakta, 2018)
Exploiting organic liquid fertilizer to lessening use fertilizer inorganic and fertilizer cage can becoming. one the solution in improving production sweet corn by exploiting land rice. Research executed  at  Waimital village, sub district of Kairatu,  sub-Province Seram  Part of West. Research take place from Desember 2013 to Maret, 2014.  The research was conducted using a randomized block design consisting of no fertilizing (0 ml / L), application of  POC (7.5 ml/L, 15 ml/L, 22.5 ml/L, and 30 ml/L)  and application time  2 MST (W1) , 2, 4 MST (W2), and 2,4,6 MST (W3). Each treatment consisted repeated that there are 30 treatment  attempt. The result showed that organic liquid fertilizer having an effect on reality to is high crop, wide  leaf, long  cob, and  cob weight. Concentration organic liquid fertilizer 30 ml/L yielding production cob weight best equal to 271.35 g/cob. Application time have an effect on reality to is high  crop and wide leaf, while cob length and cob weight do not have an effect on reality. Application time times namely : 2,4, and 6 MST (W3 ) the best  results in the appeal of other treatments. Best combination shown by treatment  concentration 30 ml / L with application time 3 times namely : 2, 4, and 6 week after planting ( N4W3).